Benefits of Forgiveness in Individuals with High Blood Pressure: Na Integrative Review (Research, Society and Development, 2021)
Objective: To identify available evidence in the literature regarding the benefits of forgiveness in individuals with high blood pressure. Method: Integrative literature review carried out in the PubMed, CINHAL, LILACS, BDENF and SCIELO databases in February and March 2020. To guide the study, the guiding question was defined: “What evidence is available in the literature about the benefits of forgiveness in individuals with high blood pressure?”. For its elaboration, the PICO strategy was used. Original articles in Portuguese, English and Spanish were included. Results: 242 publications were identified, six of which comprised the sample. There were five different benefits for individuals with high blood pressure after forgiveness training. This study identified 5 benefits of forgiveness for individuals with high blood pressure, whose citation frequency in the studies included in this review was as follows: blood pressure reduction five times; decrease in heart rate three times. Conclusion: It is considered as a limitation of the research the lack of studies that address the proposed objective, and it is not possible to significantly assess the benefits of forgiveness on the health of hypertensive individuals.